A one-dimensional switchable dielectric material with Pd uptake function: [(CH2)3NH2S]2BiCl5. Issue 89 (20th October 2020) - Liu, Yu-Ting; He, Lei; Shi, Ping-Ping; Ye, Qiong; Fu, Da-Wei
Abstract : [(CH2 )3 NH2 S]2 BiCl5 has dielectric switching and Pd uptake functions, and its adsorption can be monitored by changes in dielectric properties. Abstract : A semiconductor material [(CH2 )3 NH2 S]2 BiCl5 (1) exhibits dielectric switching and Pd uptake functions. The thioether group in 1 provides an opportunity for Pd uptake. After 1 adsorbs Pd, the dielectric switching disappears, so that Pd adsorption can be monitored by dielectric measurements. Moreover, the material becomes an insulator after adsorbing Pd.